Preplant Soil Incorporation of Compost to Mitigate Replant Disease: Soil Biological Factors Associated with Plant Growth Promotion in Orchard Soil. Issue 4 (2nd October 2018) - Watson, Tristan T.; Nelson, Louise M.; Forge, Tom A.
Abstract: Preplant soil incorporation of compost has previously shown potential to suppress Pratylenchus penetrans populations and improve replant establishment of newly planted fruit trees at old orchard sites. Using a greenhouse experiment, we evaluated the effects of preplant incorporation of three compost amendments (agricultural waste compost, yard trimmings compost, and municipal waste compost) on growth of apple seedlings, P. penetrans populations, microbial populations associated with soil suppressiveness, and microbial activity using soil collected from three orchard sites. We also aimed to identify the biological factors that were most strongly associated with enhanced plant growth in compost-amended soil. In four out of nine compost type × soil combinations, compost improved apple seedling growth relative to the control. In four out of nine compost type × soil combinations, compost reduced P. penetrans root infestation relative to the control, and in one compost type × soil combination, compost amendment increased P. penetrans root infestation. Composts stimulated soil microbial activity and abundance, resulting in greater populations of Pseudomonas spp. in soil in seven of the nine compost type × soil combinations. In a step-wise multiple linear regression, P. penetrans root infestation and the total abundance of fungi in soil accounted for the most variance in plant biomass, with increases in both variables correlated with reduced seedling biomass. Overall, composts show variability in the capacity to promote the establishment of fruit trees in orchard soil. Future research should be directed toward understanding variability in compost-induced plant growth promotion among different orchard soils and compost types.